CONTINUOUS GIRDER BRIDGE STRUCTURAL DESIGN MANADO-BITUNG TOLL ROAD - Siswaji, Vincent
In the construction of the Manado-Bitung Toll Road, there is an obstacle in the form of a valley approximately 55 meters deep from the planned elevation. Therefore, a bridge is needed to connect the ravine. In this final design assignment, the author will design a bridge at this location. Based on the geographical conditions, tall pillars are needed to support the bridge structure. The pillars used on the Pinokalan Bridge reach a height of 41 meters, so the lateral deformation that can occur in earthquake conditions will be very large so that using a simple support system becomes less technically feasible. If a simple support system is used, a bearing system with high stiffness is required. Therefore, a continuous girder bridge system is used but still uses PCI girders. In addition, the location of the bridge is in Seismic Design Category D so the author also conducted a pushover analysis to design the bridge pillars.